STEM-22. TARGETING REPLICATION STRESS RESPONSE FOR GLIOMA STEM CELL SPECIFIC CYTOTOXICITY. (12th November 2021) - Clough, Emily; Ballinger, Tracy; Semple, Colin; Strathdee, Karen; carruthers, ross
Abstract: BACKGROUND: Evidence suggests treatment resistant glioma stem cells (GSCs) drive glioblastoma (GBM) recurrence. Current treatments fail to eradicate GSC and novel GSC targeting therapies are a priority. GSC exhibit elevated DNA replication stress (RS) versus non GSC tumour cells driving constitutive DNA damage response (DDR) activation and efficient DNA repair. We previously demonstrated that targeting RS response with combined ATR and PARP inhibition (CAiPi) (VE821 and Olaparib) provides potent GSC specific cytotoxicity. In this study we investigated the underlying DDR phenotype which determines this vulnerability. RESULTS: Paired GSC enriched ('GSC') and GSC depleted, differentiated ('bulk') populations were cultured from GBM specimens in neurobasal media with growth factors or serum containing media respectively. GSC exhibited reduced survival following exposure to CAiPi versus bulk. CAiPi significantly increased 53BP1 G1 phase nuclear bodies (53BP1NBs) in GSC, which are known to shield under-replicated DNA in actively transcribed genes. Mapping the genomic distribution of endogenously occurring replication dependent DNA double strand breaks via Breaks Ligation In Situ Sequencing (BLISS), revealed reduced intragenic DSB in long actively transcribed genes in GSC versus bulk at baseline, suggesting a reliance upon transcription coupled DSB repair in GSC. RNA seq demonstrated CAiPi-induced transcriptomic alterations in GSC including replication regulation and initiation. DNA fibre assay showed that CAiPi increased GSC new origin firing which correlated with PARP trapping. GSCs were rescued from CAiPi by roscovitine induced inhibition of excess origin firing. CAiPi is potently radiosensitizing by clonogenic assay and we demonstrated murine blood brain barrier penetration of CAiPi utilising VE822 and pamiparib in vivo . CONCLUSION: Dysregulation of origin firing by CAiPi exposes a GSC specific vulnerability which results in DNA under-replication and abrogation of proficient DNA repair seen at long actively transcribed genes and has potential to be clinically translated as a GSC specific cytotoxic therapy.